ANALISIS PERMINTAAN IMPOR GANDUM DAN TEPUNG TERIGU DI INDONESIA - Hastuti Hastuti (Universitas Teuku Umar, 2016)
The development of wheat flour industry in Indonesia faces a dilemma. Wheat flour industry have an important role in the development of local industry, employment absorption and creates tax revenue the government, but the industry significantly uses large amount of foreign exchange to import those products. To meet the domestic needs of wheat flour, Indonesia imports not only wheat but also wheat flour. The purpose of this study is: (1) to identify the demand for imports of wheat and wheat flour in Indonesia, and (2) to analyze the factors that influence the demand for imports of wheat and wheat flour in Indonesia. The methods used in this research are quantitative descriptive analysis and estimation methods to estimate model parameters using the Ordinary Least Squares. The data used is secondary data with the time series data from 1984 - 2014. The Demand of wheat imports in Indonesia continues to increase as the development of wheat flour industry. Otherwise, The import of wheat flour in Indonesia have trend to decline. The demand for imports of wheat in Indonesia is influenced by the price of wheat import, the production capacity of wheat flour industry, and income per capita, while the demand for imports of wheat flour is influenced by import tariffs on wheat flour, the price of wheat flour domestic, labor, national income, and the exchange rate.